2022
DOI: 10.2298/tsci210216203l
|View full text |Cite
|
Sign up to set email alerts
|

Critical heat flux analysis of divertor cooling flow channel in fusion reactor with CFD method

Abstract: Situated at the bottom of the vacuum vessel, the divertor extracts heat and ash produced by the fusion reaction, minimizes plasma contamination, and protects the surrounding walls from thermal and neutronic loads. The vertical targets of divertor are designed to be able for up to 20 MW/m2 high heat flux. It is a great ordeal for both the material performance and the cooling ability. Critical heat flux (CHF) margin is very crucial during the design of divertor. ANSYS FLUENT is used in this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Wang et al [16] q OFI = 0.9( P h Pw )q sat 87.75 106.01 R = T out −T in T sat −T in = 0.9( P h Pw ) Al-Yahia & Jo [18] q OFI = 0.8q sat ( P h Pw )( p 1.12 ) 0.4 112.89 157.19…”
Section: Assessment Of Existing Ofi Correlationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang et al [16] q OFI = 0.9( P h Pw )q sat 87.75 106.01 R = T out −T in T sat −T in = 0.9( P h Pw ) Al-Yahia & Jo [18] q OFI = 0.8q sat ( P h Pw )( p 1.12 ) 0.4 112.89 157.19…”
Section: Assessment Of Existing Ofi Correlationsmentioning
confidence: 99%
“…In a recent study, there is a case of evaluating the CHF of a swirl tube by simulating the fusion cooling system conditions through computational simulation method. Li et al [16] calculated the CHF of a one-side high heat loaded swirl tube under the conditions of a pressure of 30 bar, a flow rate of 0.7-2.8 m 3 h −1 , and sub-cooling of 36 • C-144 • C using computational fluid dynamic (CFD). It is noteworthy that the calculation result was derived that sub-cooling and CHF do not have a linear proportional correlation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…; p = liquid specific heat (J kg −1 • K); P h = heated perimeter (m); P w =wetted perimeter (m); A=heating area [mm 2 ] (3) re-learn the model using all the normal values; (4) calculate the error between the learned model and the normal value (the error is calculated using the median absolute deviation (MAD); and (5) repeat the algorithm until it reaches a user-specified convergence value. The performance of this model was evaluated using a determinant (R 2 ), where R 2 is a measure of how well the estimated model fits all the data, and it can be obtained by (14). R 2 has a value ranging between 0 and 1, indicating that the model has learned.…”
Section: Assessment Of Existing Ofi Correlationsmentioning
confidence: 99%
“…where In recent studies, many studies have been conducted to evaluate the critical heat flux safety margin under oneside high heat load conditions inside the tokamak. Xiangyu Li et al [14] evaluated the CHF of mono-block plasma facing component with twisted tape inserted through computational fluid dynamics (CFD) simulation and compared it with experimental values. As a result, the experimental and calculated values showed an error rate of up to 32%, and this results showed that CHF could be accurately predicted through CFD simulation even under high-pressure, high-velocity, and high-temperature fluid conditions.…”
Section: Introductionmentioning
confidence: 99%